2014
DOI: 10.1186/1471-2474-15-388
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic granulomatosis with polyangiitis (Churg-Strauss syndrome) presenting as diffuse myositis

Abstract: BackgroundEosinophilic granulomatosis with polyangiitis is a complex multisystemic syndrome with heterogeneous presentation. Most often, there is a clinical history of asthma or other atopic conditions, and current presentation generally includes signs of cutaneous or pulmonary involvement. Very few reports described myalgia or weakness as the chief complaint. Of these, only a few included muscle biopsy evaluation and none showed convincing evidence of primary myositis. We believe this report is the first to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
2
9
1
1
Order By: Relevance
“…There have been few case reports of inflammatory myopathy in EGPA, and only one recurrent myositis case included a detailed description on muscle pathology. 3 MR images together with muscle pathology in our case confirms the presence of vasculitis in skeletal muscle. It is interesting that one retrospective study found proximal limb weakness in 6 of 24 EGPA patients with peripheral neuropathy had proximal limb weakness, which might have been concomitant skeletal muscle involvement that was overlooked clinically.…”
Section: Jcnsupporting
confidence: 79%
“…There have been few case reports of inflammatory myopathy in EGPA, and only one recurrent myositis case included a detailed description on muscle pathology. 3 MR images together with muscle pathology in our case confirms the presence of vasculitis in skeletal muscle. It is interesting that one retrospective study found proximal limb weakness in 6 of 24 EGPA patients with peripheral neuropathy had proximal limb weakness, which might have been concomitant skeletal muscle involvement that was overlooked clinically.…”
Section: Jcnsupporting
confidence: 79%
“…It manifests clinically in three stages, initially as allergic cold and asthma, followed by eosinophilic infiltration of the lung and intestines and systemic vasculitis. Myositis is a rare muscle manifestation of the disease and presents with myalgia, fever, and muscle weakness . Myositis in Churg–Strauss syndrome may not only concern all muscles resulting in polymyositis but may occur focally as orbital myositis .…”
Section: Resultsmentioning
confidence: 99%
“…One suggestive case report by Parent et al described a case of eosinophilic granulomatosis with polyangiitis (EGPA) presenting as diffuse myositis. In that report, a muscle biopsy showed necrotizing vasculitis with true myositis ( 46 ), and the main location of inflammation was thought to be both the vessels that supply the muscles and the muscle itself. Our case shows that both perimysial and endomysial infiltration of neutrophils can accompany vasculitis ( Fig.…”
Section: Discussionmentioning
confidence: 96%